DECOMPOSITION ANALYSIS OF CO2 EMISSION IN INDONESIA’S ENERGY-INTENSIVE INDUSTRIES - Andri Febriyanda; Deni Kusumawardani; Muhammad Adnan (RADJA PUBLIKA, 2025)
The growth of the industrial sector through industrialization greatly affects the increase in CO2 emissions. Energy conservation and diversification policies need to be carried out to reduce CO2 emissions, especially in energy-intensive industries. This study aims to decompose and analyze the factors that cause changes in CO2 emissions using the LMDI method. The data used in this study was sourced from large and medium industry surveys during the period 2010-2015. The results show that the effects of changes in economic activity, industrial economic structure and energy intensity are the main factors that contribute to the increase in CO2 emissions in the cement, food, pulp & paper, chemical and textile industries. The structural effects of energy composition and emission coefficients have not shown a significant contribution to the increase or decrease of CO2 emissions. Policy recommendations to reduce CO2 emissions in energy-intensive industries are to encourage energy efficiency and transition through the use of energy-saving and low-carbon technologies, as well as revitalize old and inefficient technologies.